O legado histórico da organização política do serviço social brasileiro e seus desafios na atualidade - Monteiro, Maria da Guia da Silva (2020)
This dissertation presented and discussed as entities representing the social worker category, especially ABEPSS, CFESS / CRESS and ENESSO, preventing, strengthening, maintaining and deepening the strategic social direction of the professional Social-Political project of the Brazilian Social Service. For this analysis, we established the first decade of the 2000s (2010- 2018) as a time frame, considering that these years make up the decade closest to the present. We had as sources of research data, exclusively, the websites of the following entities above. From the Brazilian Association of Teaching and Research in Social Work - ABEPSS, we selected the ABEPSS Itinerant project and the Plan of Fight in Defense of Work and Training and Against the Precariousness of Higher Education, as well as the ABEPSS Curricular Guidelines and the National Internship Policy , documents that were published by the entity, constituting the basis of the professional training policy of social workers. From the Federal Council of Social Work, we chose as research material the final reports of the National Meetings, according to the time frame of the research, as well as some Resolutions published by CFESS that had rights with the training and professional work of social workers. And from ENESSO, we selected the Notebooks of Deliberations of the National Social Service Students' Meetings - ENESSO, and some booklets published by the entity on topics related to the process of training Social Work students. We analyzed this data set according to each representative entity, evidenced, its articulation or not with the ethical-political principles of the professional project, comparing with the literature that the profession has historically built, with regard to its current professional project. We agree with Netto (2009a), based on Marx's thought, that the researcher's role in the investigation, having to apprehend as multiple determinations and mediations of the researched phenomenon, to analyze its internal dynamics and functioning and to investigate the connection that there is between them. Therefore, our analysis shows that the entities highlighted in this research, are of paramount importance for the maintenance, deepening and advancement of the strategic direction of the critical social service's ethical-political project, even in adverse circumstances to its fundamentals.